PENGARUH PROFITABILITAS, SOLVABILITAS, DAN STRUKTUR AKTIVA TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2018 - Winda Oktafianti (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2020)
The purpose of this study was to determine the influence of profitability, solvency, and asset structure on the value of manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2018. This type of research is quantitative, with a study population of 158 manufacturing companies listed on the IDX and only 61 companies which is used as a research sample because it is in accordance with predetermined criteria. This study uses only one year of research, namely in 2018. Processed company data, viewed through the company's financial statements published by the Indonesia Stock Exchange (IDX) and tested using the SPSS program version 16.0. Based on calculated used of SPSS program that profitability has a significant effected on company value. Solvency and asset structure have no significant effected on company value.